STRATEGI PERSUASIF DALAM PENGEMBANGAN HUBUNGAN SOSIAL RELIGIUS ANTARA SISWA DAN TENAGA KEPENDIDIKAN DI LINGKUNGAN MTSN 2 PAMEKASAN - Jamiludin Usman; Mohammad Hidayatul Ahsan (re-JIEM (Research Journal of Islamic Education Management), 2019)
The persuasive strategy in developing religious social relations in schools is needed not only to encourage school members to behave well in the school environment but must be able to instill religious values in the school community until the religious soul is embedded in them to behave both in internal and external environments. This study uses a qualitative phenomenological approach. The results of this study that the strategies carried out by schools are a) activities of greetings at the school gate, the Dhuha prayer in congregation, memorizing juz amma, and the midday prayer. b) the measurement is seen from the attitude of students and student participation in activities. c) how to maintain it by holding Islamic activities. d) the application of growing social sense is increasing. Suggestions for this research are: a) any results obtained by researchers should be a reference for internal improvement for the institution. b) institutions must continue to maintain good social relations between students and educators so that in the future the institution will be more advanced and of good quality. c) routine evaluation of the strategies that have been used.